Exploring and Comparing Content Validity and Assumptions of Modern Theory of an Integrated Assessment: Critical Thinking-Chemical Literacy Studies - Sadhu, S.; Ad'hiya, E.; Laksono, E. W. (Jurnal Pendidikan IPA Indonesia, 2019)
The development of chemical literacy as well as critical thinking, are a prominent objective of science education and become essential skills in the 21st century. The stress has not been given to the measurement of both skills together in chemistry content in high school. Another problem shows in developing an instrument in which teachers often do not know whether the content and construct that they developed in the tool can measure the skill that supposed to be measured. The first step the teacher should do is studying the content validity when an instrument has been constructed and also psychometric testing is needed. Hence, this is addressed for exploring the content validity evidence, even assumptions for the modern theory in integrated assessment for measuring students’ chemical literacy and critical thinking. Also, comparing a result of content validity and assumptions for modern theory to know which is mandatory for research instrument. The initial integrated assessment consists of 37 items. Content validity was first piloted under a review of six experts and also 133 participants involved to determine the assumptions of modern theory in integrated assessment. From this study, it can be confirmed that the development of the integrated assessment on the content validity can be used to measure 13 integrated skills of chemical literacy and also critical thinking in chemical equilibrium, and an assumption for modern theory met with the standard of the valid instrument. In general, to know the quality of the items test using more sophisticated statistical analysis, the integrated assessment is appropriate for measuring the big-scale of the paper-pencil test. The outcome of this research will help teacher/lecturer in the analysis quality of an assessment that will be used in student’s evaluation